Jpop: Fenomena Englishization dalam Lirik Lagu Berbahasa Jepang - Gede Satya Hermawan (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2013)
This article discusses about Jpop (Japanese Popular Music). It explores englishization in JPop(Japanese Popular Music) in the light of recent theoretical development of sociocultural linguistic.This article also shows of englishization can refashions diction in a song lyrics, and draws attention tothe way that sociocultural becames a force to provoke such refashioning.